INOVASI KURIKULUM PAI: INTEGRASI ANTARA KURIKULUM NASIONAL DAN PENDIDIKAN ISLAM DI ERA DIGITAL - Alpata, Ahmad Rudi; Rahmadan; Habib Zainuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of the national curriculum shows the importance of an interdisciplinary approach in Islamic Religious Education (PAI) learning that can be integrated with science, technology, and language. However, the implementation of the PAI curriculum still faces obstacles, such as limited access to technology and lack of teacher training. This study aims to explore effective methods in the integration of the PAI curriculum with 21st century competencies, as well as identify key components for adaptation. The methods used include literature analysis and case studies on the application of digital technology in PAI learning. The results of the study show that the blended learning approach can increase the relevance of PAI, ensure alignment with modern educational goals, and support students' moral and spiritual development. This research also emphasizes the importance of overcoming challenges such as the digital divide and the lack of teacher skills in using technology, so that the benefits of technology in education can be felt equally. With the right steps, the integration of technology in the PAI curriculum can improve the overall quality of education, answering modern challenges without neglecting fundamental religious principles.